Upregulation of cluster of differentiation 36 mRNA expression in peripheral blood mononuclear cells correlates with frailty severity in older adults. Issue 3 (17th April 2022) - Lee, Chung‐Sheng; Chang, Chin‐Hao; Chen, Chin‐Ying; Shih, Chih‐Yuan; Peng, Jen‐Kuei; Huang, Hsien‐Liang; Chen, Pei‐Yun; Huang, Tse‐Le; Chen, Ching‐Yu; Tsai, Jaw‐Shiun
Abstract: Background: Aging‐associated frailty has been connected to low‐grade chronic inflammation and also to progressive monocytic activation. CD36 (cluster of differentiation 36, platelet glycoprotein 4 or fatty acid translocase) has been shown to induce the expression of pro‐inflammatory cytokines and to activate macrophage connected inflammation. This study aims to examine whether the expression of CD36 is up‐regulated among frail older adults. Methods: The demographic data, Fried Frailty Index, metabolic and inflammatory parameters of our observational study were obtained from the comprehensive geriatric assessment programme of a hospital‐based outpatient department. The mRNA isolated from the peripheral blood mononuclear cells (PBMCs) was used to determine the levels of CD36, tumour necrosis factor alpha (TNF‐α), and CXC chemokine ligand‐10 (CXCL10) mRNAs with real‐time polymerase chain reaction (PCR). Results: A total of 189 older adults (58% female) were included in the analysis, and the mean age was 77.19 ± 6.12 years. The numbers of participants who fitted in the groups of robust, pre‐frail, and frail were 46, 106, and 37, respectively. Our data showed that CD36 mRNA expression levels in PBMCs were the highest in the frail group (1.25 ± 0.53 in robust, 2.13 ± 1.02 in pre‐frail, and 2.78 ± 1.15 in frail group, P < 0.001). Further regression analyses revealed that CD36 mRNA levels were positively correlated with both the pre‐frail and frailty status in the univariate analysis (both P 's < 0.001). What might suggest something worthy of further investigation is that, with potential confounders being adjusted for, CD36 remained as an independent factor that positively correlated with the pre‐frail and frailty status in the multivariable analysis ( P < 0.001). Conclusions: CD36 mRNA levels in PBMCs in robust older adults are significantly lower than in pre‐frail and in frail. Our findings suggest that CD36 mRNA levels in PBMCs may be considered a potential biomarker for frail severity.